The Existence of the Rights of Indigenous People in the Implementation of Regional Autonomy - Helben Gainau; Ronny A. Maramis; Merry Elisabeth Kalalo; Caecilia J. J. Waha (International Journal of Applied Business and International Management, 2023)
In essence, regional autonomy is given to the people as a legal community unit that is given the authority to regulate and manage its own government affairs given by the central government to the regions and in its implementation is carried out by the regional head and DPRD with the assistance of regional apparatus.The goal of this research is to examine and analyze how indigenous peoples' rights are construed legally on a national and international level, as well as how their protection can be used as a tool for participation in the implementation of regional autonomy. It also aims to produce conclusions about the existence of indigenous peoples' rights in the implementation of regional autonomy.A statutory approach, conceptual approach, historical approach, case approach, and comparative approach are some of the study methods utilized in normative legal research. 25  2The results showed (1) The concept of indigenous peoples in international law and international indigenous law is the main subject of international law, (2) Strictly speaking, there is no recognition and regulation of the rights of indigenous peoples in national legal instruments to develop their existence and culture and involve indigenous peoples in aspects of development programs and projects, (3) The involvement of indigenous peoples in the administration of local government is not yet optimal, including the recognition of customary government organisational structures.